Conflict Management at Madrasa - Setiawati, Rini; Mubasit, Mubasit; Cahyadi, Ashadi (Journal of Advanced Islamic Educational Management, 2022)
In carrying out their duties and responsibilities, they are always faced with various factors, such as differences in opinion from each and functional duties. This type of research is descriptive qualitative with data collection techniques using interviews, observation, and documentation. The data sources in this study were the Head of the Madrasa and one educator of MTs Nur El-Ehsan Katibung South Lampung. Checking the validity of the data is done by triangulating the technique, namely as a data validity tester by checking the data on the same source but with different techniques. From the results of the study, it was found that the implementation of conflict management to solve any problems that occur at MTs Nur El-Ehsan Katibung South Lampung, has been running. This can be seen from the results of the observation activities that the authors carried out in the study, namely from the three indicators including planning, implementation, and evaluation. However, the three indicators have not run optimally because the implementation of conflict management at MTs Nur El-Ehsan Katibung South Lampung has not been carried out effectively and efficiently